Short introduction to corporate finance - Raghavendra Rau (Cambridge short introductions to management, 2017)
"The Short Introduction to Corporate Finance provides an accessibly written guide to contemporary financial institutional practice. Rau deploys both his professional expertise and experience of teaching MBA and graduate-level courses to produce a lively discussion of the key concepts of finance, liberally illustrated with real-world examples. Built around six essential paradigms, he builds an integrated framework covering all the major ideas in finance over the past half-century. Ideal for students and practitioners alike, it will become core reading for anyone aspiring to become an effective manager"--